2022
DOI: 10.1002/cmdc.202200422
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics‐Based Urine Biopsy for Cancer Diagnosis: Recent Advances and Future Trends

Abstract: Urine biopsy, allowing for the detection, analysis and monitoring of numerous cancer-associated urinary biomarkers to provide insights into cancer occurrence, progression and metastasis, has emerged as an attractive liquid biopsy strategy with enormous advantages over traditional tissue biopsy, such as non-invasiveness, large sample volume, and simple sampling operation. Microfluidics enables precise manipulation of fluids in a tiny chip and exhibits outstanding performance in urine biopsy owing to its minimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 180 publications
0
1
0
Order By: Relevance
“…In addition to infection detection, a bladder-on-a-chip system has been used for noninvasive diagnostic purposes. Wang et al developed a protein microarray chip to capture bladder cancer cells and biomarkers from urine samples [152]. Similarly, Lin et al were able to have a quantitative measurement of biomarker concentration using a bead-based enzyme-linked immunosorbent assay [153].…”
Section: Bladder-on-a-chipmentioning
confidence: 99%
“…In addition to infection detection, a bladder-on-a-chip system has been used for noninvasive diagnostic purposes. Wang et al developed a protein microarray chip to capture bladder cancer cells and biomarkers from urine samples [152]. Similarly, Lin et al were able to have a quantitative measurement of biomarker concentration using a bead-based enzyme-linked immunosorbent assay [153].…”
Section: Bladder-on-a-chipmentioning
confidence: 99%
“…Their results showed that the DLD particle size-based sorting method could provide a rich and diverse population of SSCs. DLD technology also shows excellent potential in isolating circulating tumor cells; CTCs are separated from the blood or urine [11,12] by a DLD chip and are diagnosed with related cancers. Tang, H. et al [13] used a new design method of extension optimization to shorten the device and flexibly manipulate the cell motion path for efficient sorting of the circulating tumor cells (CTCs).…”
Section: Introductionmentioning
confidence: 99%